Factors influencing the duration of hospitalization of patients with schizophrenia - Velelekou, Anna; Papathanasiou, Ioanna V.; Alikari, Victoria; Papagiannis, Dimitrios; Tsaras, Konstantinos; Fradelos, Evangelos C (Medicine and Pharmacy Reports, 2022)
Introduction. Severe mental disorders represent an important and large proportion of healthcare resource utilization and are associated with increased hospitalization rates and costs. Given the high percentage of total hospital days and costs associated with caring for people with psychotic disorders, a better understanding of the factors that determine the duration of hospitalization of patients with such disorders is imperative. Purpose. The aim of the present study was to investigate socio-demographic, clinical and psychosocial characteristics of patients with schizophrenia, admitted to a Greek public psychiatric hospital, and the relationship between these characteristics and duration of hospitalization among these patients. Methods. This is a cross-sectional study. The study sample consisted of 103 patients diagnosed with schizophrenia (F-20). The collection of data was performed by using the NEO-Five Factor Inventory, the Connor-Davidson Resilience Scale (CD-RISC25), Multidimensional Scale of Perceived Social Support, (MSPSS), Positive and Negative Syndrome Scale (PANSS), Global Assessment of Functioning scale (GAF) for assessing key personality factors, psychological resilience, social support, symptom severity and the severity of the disease, respectively. Descriptive analyses and inferential statistic methods were applied. Correlation between socio-demographic, psychosocial or clinical characteristics with the length of stay were explored. In addition, linear regression analysis was performed in order to examine predicting factors for the duration of hospitalization. All statistical analysis was performed using SPSS v.25. Results. The mean age of the sample was 43.9 (SD = ±11.4) years, 67% of patients were men, and the mean length of hospitalization was 40.7 days. Factors found to be significantly associated with length of stay in the overall sample include the previous admissions (p=0.010), the type of admission (compulsory or voluntary) (p=0.017), bed rest (p=0.043) and duration of bed rest (p=0.002), and the existence of social support networks especially from friends (p=0.018). Conclusions. Our findings indicate that basic psychosocial and clinical factors were associated with the duration of hospital stay. Duration of hospitalization results from a complex interface between characteristics and activities of the health system, patient, and clinician’s influence on discharge timing, which requires additional study. Our findings further warrant the need for policymakers to consider socio-demographic status, psychosocial and clinical factors when allocating resources to hospitals caring for patients with severe mental disorders.